Method of surgical renewal of continuity of pelvic ring in children with extrophy of bladder - O. V. Shchekin (Zaporozhye State Medical University, 2013)
Section of back and interbone sacroiliac ligaments from both sides, at extrophy of bladder, instead of osteotomу of iliac bones allows easily to liquidate large diastasis between pubic bones, to carry out them osteosintez, to normalize the location of hip joints and enables to carry out plastic of bladder. Thus there is no bleeding, as ligament have not blood vessels, and there is no cutting or damage of ligatures in the place of osteosinthesis of pubic bones. 3 children aged from 3 weeks to 1 year are operated according to this method. Complications were not present.